Biodegradability and mechanical behaviour of sugar palm starch based biopolymer - Sahari, Japar; Sapuan, Mohd Salit; Zainudin, Edi Syams; Maleque, Md. Abdul (Science Publications, 2014)
A new Sugar Palm Starch (SPS) based biopolymer was successfully developed using glycerol as plasticizer. The effect of glycerol concentration (viz., 15, 20, 30 and 40 by weight percent) to the mechanical properties of plasticized SPS biopolymer was investigated. From this investigation, it was found that the 30% glycerol concentrated biopolymer showed the highest flexural strength and impact with the value of 0.13 MPa and 6.13 kJ/m2 respectively. Later, the above 30% glycerol biopolymer was undergone through weathering and biodegradation test. The biodegradability test showed 78.09% of tensile strength lost after 72 h of weathering testing period. Meanwhile, the weight loss (%) of the same biopolymer was 63.58% after 72 h of biodegradation test.